IMAGINED COMMUNITY, IMAGINED IDENTITY, AND INVESTMENT IN LANGUAGE LEARNING: AN AUTOETHNOGRAPICAL ACCOUNT - Nghia, Nguyen Xuan (VNU Journal of Foreign Studies, 2020)
Language learning, viewed through post-structuralist prism, is not the practice of the individual per se but a social practice characterized by the multiple and changing learner identity in direct contact with inequitable power relations (Norton, 2013). Not always does it deal with the immediate identity of the learner in the real-time setting, but also identities defined through “the power of the imagination” in “not immediately accessible and tangible” communities (Norton, 2013, p.8). It is this set of imagined identities that governs the learner’s investment in meaningful learning practices, which in turn provides him/her with a wide range of capital. With this departure point in mind, in this autoethnography-based study, I told my own story of language learning and arrived at two findings. One, my identities as a language student, a language teacher, and a language teacher-researcher formed primarily with social factors, especially my imagination of social power gains. And two, my investments in language learning were regulated by these imagined identities and done so in ways that investment was prioritized over the identity related to higher social status and that where my identity was not invested, I took the initiative to invest to realize it.